Axiological dimensions of the Bible concept HUMILITY in Ukrainian political media discourse - Levko, Oleksandr (Current issues of Ukrainian linguistics: theory and practice, 2017)
The article analyses the evaluation of the concept HUMILITY in the Ukrainian political media discourse with the particular focus on comparative investigation of the "humility words" semantics, based on the religious and political publications of the internet portals "Dzerkalo tyzhnja", "Ukrajinskyj Tyzhden", "Ukrajinska Pravda", "Gazeta po-ukrajinsky" and "Viche". It is established that Christian value of humility acquires ambiguous evaluative semantics in the modern media discourse. It is demonstrated that the words of humility are mostly used with negative connotations in political media texts. Particularly, the word "humble" is shown to have the following meanings as "weak", "inactive", "passive", "compliant", "weak-willed", "powerless". It is noted that the words of humility may be used as one of the means of hierarchs' discrediting for their outward humility. It is also revealed that the word "humility" acquires positive evaluative semantics when used to convey the meanings "not overestimating one's accomplishments and abilities", "not exaggerating one's traits", "adequate self-assessment", "restrain of one's ambitions", "avoidance of arrogance and boastfulness".
Keywords: political media discourse, axiology, concept, humility, values, category of evaluation.